2016
DOI: 10.1364/oe.24.013288
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of coherent free space optical communications with a double-stage fast-steering-mirror adaptive optics system depending on the Greenwood frequency

Abstract: The Greenwood frequency (GF) is influential in performance improvement for the coherent free space optical communications (CFSOC) system with a closed-loop adaptive optics (AO) unit. We analyze the impact of tilt and high-order aberrations on the mixing efficiency (ME) and bit-error-rate (BER) under different GF. The root-mean-square value (RMS) of the ME related to the RMS of the tilt aberrations, and the GF is derived to estimate the volatility of the ME. Furthermore, a numerical simulation is applied to ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…17,18 The mixing efficiency and the BER performances of the closed-loop AO integrated with the coherent optical communications were analyzed. [19][20][21] Different AO approaches for OGS were presented and compared. 22 Although the AO was proven to be a very promising technique that can largely improve the performances of the space-to-ground optical communication links, the complex systems and expensive costs limit its application.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 The mixing efficiency and the BER performances of the closed-loop AO integrated with the coherent optical communications were analyzed. [19][20][21] Different AO approaches for OGS were presented and compared. 22 Although the AO was proven to be a very promising technique that can largely improve the performances of the space-to-ground optical communication links, the complex systems and expensive costs limit its application.…”
Section: Introductionmentioning
confidence: 99%
“…FSMs have been widely used in many fields, such as imaging [2,3] and laser processing systems [4], free-space optical communications [5,6], and laser weaponry [7,8]. With a high bandwidth, FSMs are capable of fast response and good disturbance rejection [9].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al . 12 experimentally studied the influence of the GF on FSOC performance, and the experimental results showed that a higher bandwidth is necessary to guarantee communication quality with increasing GF. Cao et al .…”
Section: Introductionmentioning
confidence: 99%